Model peningkatan nilai perusahaan melalui struktur modal pada industri perbankan di bursa efek indonesia - Ariyanti, Rizka; Mujiyono, Mujiyono (JURNAL LITBANG KOTA PEKALONGAN, 2017)
This study aims to examine and analyze the increase in the value of the company through its capital structure, profitability and firm size, ( Studies in Bank Go Public in Indoseia Stock Exchange 2010 -2014 ) To test these variabels, the researchers use the 27 companies that went in public Indosia Stock Exchange. This type of research is explanatory research, Tehknik data collection using documentary technique. The data used in this research are secondary data from financial statetements published by banking companies during 2010 -2014 Furthermore, the data collected was analyzed quantitatively by using multiple regression using Eviews program version 8.1 The result showed that the variables Size does not affect the DER, Profitability significantly influence the DER, While the, Firm size affect the PBV. Profitability does not affect the PBV. DER is found as not a mediating variable that strengthen the influence of Profitabiliy, Firm size, on firm value PBV banking companies listed in Indonesia Stock Exchange.